TANGGUNGJAWAB NEGARA DALAM MENANGANI PENANKGAPAN IKAN SECARA ILEGAL DI INDONESIA - Hakim, Abdurrahman; Arif Mu'allifin, M Darin (Jurnal Rechts Vinding: Media Pembinaan Hukum Nasional, 2023)
This paper aims to describe the responsibility of the country of illegal fishing cases in Indonesian waters. The impact of Illegal fishing is hight state losses, rising unemployment, and reduced income for fishermen. The worst thing that is caused by this case is the way of other crimes such as human trafficking, the smuggling of illegal drugs, and slavery. Illegal fishing is included in transnational crime cases that often violate a country's maritime boundaries. The majority of illegal fishing violations in Indonesia are foreign-flagged fishing boats, while in some cases handled by the authorities are confirmed as Indonesian citizens. The research method used is qualitative-descriptive with library research design. This type of research includes empirical-normative research with data in the field in the form of news, journals, and books and then analyzed using the theory and rules of legislation. The results of the study indicate that there are several state responsibilities in the handle of illegal fishing is enact administrative requirements for ships and ship's crew, monitoring fishing activities, criminal sanctions and fines for illegal fishermen, diplomacy, and disputes to the International Court of Justice. From these efforts that need to be improved is a surveillance patrol following the extent of the Indonesian sea, the impositions of criminal sanctions for perpetrators and the authority to take legal actions for supervisors, and use military power for countries that don't acknowledge UNCLOS 1982.